Building a birds eye view: collaborative work in disaster response - Fischer, Joel; Reeves, Stuart; Rodden, Tom; Reece, Steve; Ramchurn, Sarvapali; Jones, David (ACM, 2015)
Command and control environments ranging from transport control rooms to disaster response have long been of interest to HCI and CSCW as rich sites of interactive technology use embedded in work practice. Drawing on our engagement with disaster response teams, including ethnography of their training work, we unpack the ways in which situational uncertainty is managed while a shared operational 'picture' is constituted through various practices around tabletop work. Our analysis reveals how this picture is collaboratively assembled as a socially shared object and displayed by drawing on digital and physical resources. Accordingly, we provide a range of principles implicated by our study that guide the design of systems augmenting and enriching disaster response work practices. In turn, we propose the Augmented Bird Table to illustrate how our principles can be implemented to support tabletop work.